2013
DOI: 10.1186/1477-7525-11-27
|View full text |Cite
|
Sign up to set email alerts
|

Cross cultural evaluation of the Warwick-Edinburgh mental well-being scale (WEMWBS) -a mixed methods study

Abstract: BackgroundWe aimed to validate the Warwick-Edinburgh Mental Well-being Scale (WEMWBS) among English speaking adults representing two of the minority ethnic groups living in the UK, self-identified as Chinese or Pakistani by background, in a mixed methods study.MethodsQuantitative data were collected in two cities in the West Midlands, UK. Item response, dimensionality, internal consistency, and construct validity of the WEMWBS were assessed in Chinese and Pakistani groups separately, using data from both citie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 24 publications
6
83
2
3
Order By: Relevance
“…Therefore, the WEMWBS scale is an instrument that will meet the needs of individual and population assessments. 5,7,9,22 Valid and reliable instruments for research are extremely important in comparisons between different contexts and samples. They are recommended when the goal is to assess the validity of an instrument, which is achieved through continuing research on the subject.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the WEMWBS scale is an instrument that will meet the needs of individual and population assessments. 5,7,9,22 Valid and reliable instruments for research are extremely important in comparisons between different contexts and samples. They are recommended when the goal is to assess the validity of an instrument, which is achieved through continuing research on the subject.…”
Section: Discussionmentioning
confidence: 99%
“…4 Other studies have shown scores of 53.5 points in a Spanish sample, 6 52.34 points in a sample of Chinese origin, and 52 points in a third sample of Pakistani origin. 7 The adequacy of the factor analysis was confirmed by KMO and Bartlett's test of sphericity, which in turn made it possible to verify the adequacy of the data for application of factor analysis. In this study, the factor analysis was suitable for processing the data, with two factors accounting for approximately 65.7% of the variance found.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…La escala ha sido validada en grupos e individuos (Maheswaran, Weich, Powell, & Stewart-Brown, 2012), en poblaciones de diferentes áreas geográficas (Lloyd & Devine, 2012;Stewart-Brown, Tennant, Tennant, Platt, Parkinson, & Weich, 2009;, con diferentes profesiones y culturas (Bartram, Sinclair, & Baldwin, 2013;Taggart, Friede, Weich, Clarke, Johnson, & Stewart-Brown, 2013), diferentes edades (Clarke, Friede, Putz, Ashdown, Martin, Blake, & Stewart-Brown, 2011), y capacidades cognitivas (Deary, Watson., Booth, & Gale, 2013).…”
Section: Tradução Adaptação Ao Espanhol E Validação Da Escala De Bemunclassified